2018
DOI: 10.14534/j-pucr.2018338707
|View full text |Cite
|
Sign up to set email alerts
|

Indirect inguinal hernia containing uterus, fallopian tube, and ovary in a term infant

Abstract: A B S T R A C TIndirect inguinal hernia is most commonly seen in infants. Prevalence is lower in girls. Both uterus and ovary including hernia sac is extremely rare. Early diagnosis and surgery is critical, since strangulation and necrosis of these organs may lead to serious conditions and infertility. Doppler Ultrasound (US) is the effective method in differentiation and diagnosis of inguinal hernias of infants. In this very rare case, according to the literature knowledge, we aimed to represent the sonograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…We recommend contralateral exploration to avoid the infant having to undergo another surgery, especially when the location is on the left in a premature subject. Many surgeons choose to explore the contralateral inguinal region at the time of the open procedure based on data from the literature that concomitant inguinal hernias occurred in 25% of females and another study reported that the contralateral patent rate in defects of the processus vaginalis in female preterm infants was as high as 76.9% [8][9][10]. A previous report states that the cure of indirect inguinal hernia can be performed laparoscopically, but this requires skill and mastery of the technique, even in the hands of highly experienced surgeons, the conversion by an open inguinal approach is 10% [9].…”
Section: Discussionmentioning
confidence: 99%
“…We recommend contralateral exploration to avoid the infant having to undergo another surgery, especially when the location is on the left in a premature subject. Many surgeons choose to explore the contralateral inguinal region at the time of the open procedure based on data from the literature that concomitant inguinal hernias occurred in 25% of females and another study reported that the contralateral patent rate in defects of the processus vaginalis in female preterm infants was as high as 76.9% [8][9][10]. A previous report states that the cure of indirect inguinal hernia can be performed laparoscopically, but this requires skill and mastery of the technique, even in the hands of highly experienced surgeons, the conversion by an open inguinal approach is 10% [9].…”
Section: Discussionmentioning
confidence: 99%